Writing legibility of selected effectors: Evidence for a generalized motor program? - Patricia Paulsen Hughes; Madison Gilliam Beanland; Tyler Danielson; Bert H. Jacobson (Karolinum Press, 2020)
The purpose of the study was to determine if a generalized motor program (GMP) exists for writing, as has been previously reported. Beginning with a 1942 experiment by Lashley, and continuing with a 1976 (Raibert) example, writers of some motor learning texts have asserted that one can write with different effectors (nonpreferred hand, mouth, foot, etc.) and the results are quite similar, thus demonstrating that writing is a generalized motor program. The task has not been reported in recent literature. In order to determine if the results reported were generalizable, the researchers recruited 31 individuals who volunteered to write a short sentence under five conditions: 1) preferred hand, 2) preferred hand with wrist stabilized, 3) non-preferred hand, 4) mouth, and 5) foot. Participants ranged in age from 19 to 75 and were grouped as follows: < 25 yrs, n = 15; 25-44 yrs, n = 6; > 44, n = 10. Although all of the samples were legible in Conditions 1 and 2, legibility deteriorated significantly in Conditions 4 and 5. Contrary to expectations, there were no significant differences between the samples produced by based on age groupings. The authors concluded that most adults cannot write legibly with their mouths or feet, contrary to what has been previously reported.